2016
DOI: 10.1039/c6ra07368a
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent CdSe quantum dot–lysozyme interaction and effect on enzymatic activity

Abstract: Size-dependent (2.5 and 6.3 nm) interaction of MPA modified hydrophilic CdSe quantum dots with lysozyme are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 69 publications
0
26
0
Order By: Relevance
“…To the best of our knowledge, the toxicity mechanisms of QDs have gradually been explored by the scientists, however, different synthetic methods of QDs own different properties, thus the results of present studies are not enough. Although the interaction between CdTe QDs and lysozyme has been investigated by spectroscopic and microscopy methods, but the inner filter effect was not considered and little work has been done about the isothermal titration calorimetry (ITC) experiment, which is an accepted method among all the available techniques to measure the thermodynamic parameters of the interactions.…”
Section: Introductionmentioning
confidence: 94%
“…To the best of our knowledge, the toxicity mechanisms of QDs have gradually been explored by the scientists, however, different synthetic methods of QDs own different properties, thus the results of present studies are not enough. Although the interaction between CdTe QDs and lysozyme has been investigated by spectroscopic and microscopy methods, but the inner filter effect was not considered and little work has been done about the isothermal titration calorimetry (ITC) experiment, which is an accepted method among all the available techniques to measure the thermodynamic parameters of the interactions.…”
Section: Introductionmentioning
confidence: 94%
“…In regards to single enzyme systems, recent work with phosphotriesterase (PTE) assembled to CdSe/ZnS core/shell QDs, which emitted at either 525 nm (4.3 ± 0.5 nm diameter) or 625 nm (9.2 ± 0.8 nm diameter) demonstrated that both QDs significantly enhanced immobilized enzymatic activity compared to enzyme in free solution; the k cat increased~4-fold while the enzymatic efficiency (k cat /K M ) increased 2-fold [82]. Although the focus of this review is exclusively on the enhancement of enzymatic activity with enzymes immobilized to QDs, we note that several reports have also indicated striking improvements in enzymatic activity when the substrate is attached to QDs, particularly as proteolytic reporters [87,88,90,[95][96][97][98][99][100][101][102][103][104][105][106][107].…”
Section: Enzyme Immobilization On Qdsmentioning
confidence: 92%
“…Nanomaterials such as silica, Ag, Au, and semiconductor QDs such as ZnO and CdSe have been found to alter the biological activity of the enzymes by significantly impacting their structure (Vertegel et al 2004;Secundo 2013;Petkova et al 2012;Zhao et al 2019;Das et al 2016). Zhao et al (2019) investigated the interaction of MPA-CdSe/ZnS with catalase(CAT) and superoxide dismutase (SOD) within hepatocytes of mice and found that hydrophobic force was involved in MPA-CdSe/ZnS binding to CAT and SOD, the primary consequence of which was an alteration in the secondary structure of enzymes (reduction in the α-helix content) (Zhao et al 2019).…”
Section: Introductionmentioning
confidence: 99%